CONTRIBUTION OF CONCENTRATION AND SPEED OF HAND REACTION TO ACHIEVEMENT OF DOWNHILL ATLET - Pamungkas, Dela Andika Tri; Kumaat, Noortje Anita (Jurnal Kesehatan Olahraga, 2019)
Downhill (MTB) is an extreme sport that is increasingly popular, even experiencing a fairly good development. Downhill branches are aimed at developing towards achievement, this can be seen from the achievements of the Indonesian contingent who won 2 gold medals during the Asian Games that have just been held in Jakarta and Palembang in 2018. In competitions, especially downhill concentrations are needed which related to the reaction speed of the hand when passing downhill tracks. The purpose of this study was to determine how much the contribution of concentration and speed of hand reactions to the performance of downhill athletes. This research was conducted on 10 national elite / professional male downhill athletes in the 2018 Series 4 Indonesian Downhill National Championship in Wonogiri, Central Java. The method used is a quantitative correlational approach, while the data collection process is carried out by performing concentration tests, hand reaction speed and time records of athletes during the race. From the results of the study can be explained: Anova results state the value of Fcount = 5,640> Ftable = 4,74. It can be said that there is a significant contribution between the variables of concentration (X1), the speed of hand reaction (X2) together on the performance of downhill athletes (Y). From the research results obtained individually the concentration variable contributes the most to the variable performance of downhill athletes. Then followed by the reaction speed of the hand. For both independent variables, special attention needs to be given to improving training so that the maximum performance of downhill athletes can be obtained. The conclusions is : 1). Concentration variable (X1) contributed 61,62%. 2). Variable hand reaction speed (X2) contributed 49,98%. 3). Individually each independent variable, concentration which has a greater contribution and together all the independent variables contribute 61,78% to the performance of downhill athletes (Y) so that overall can be generalized into the population.Keywords: Concentration, Hand Reaction Speed, Downhill.